2014
DOI: 10.1038/ismej.2014.69
|View full text |Cite
|
Sign up to set email alerts
|

Inference of interactions in cyanobacterial–heterotrophic co-cultures via transcriptome sequencing

Abstract: We used deep sequencing technology to identify transcriptional adaptation of the euryhaline unicellular cyanobacterium Synechococcus sp. PCC 7002 and the marine facultative aerobe Shewanella putrefaciens W3-18-1 to growth in a co-culture and infer the effect of carbon flux distributions on photoautotroph-heterotroph interactions. The overall transcriptome response of both organisms to co-cultivation was shaped by their respective physiologies and growth constraints. Carbon limitation resulted in the expansion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 61 publications
5
94
0
3
Order By: Relevance
“…Peptidoglycan and lipopolysaccharides are components of the bacterial cell wall and outer membrane, and both have been suggested to mediate cell-cell recognition and signaling (Dworkin, 2014). Similar changes have been observed in different Synechococcus strains in response to co-culture (Tai et al, 2009;Beliaev et al, 2014). In response to nutrient starvation, the expression of these genes either did not change, or they were less abundantly expressed (Tolonen et al, 2006;Martiny et al, 2006;Thompson et al, 2011).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Peptidoglycan and lipopolysaccharides are components of the bacterial cell wall and outer membrane, and both have been suggested to mediate cell-cell recognition and signaling (Dworkin, 2014). Similar changes have been observed in different Synechococcus strains in response to co-culture (Tai et al, 2009;Beliaev et al, 2014). In response to nutrient starvation, the expression of these genes either did not change, or they were less abundantly expressed (Tolonen et al, 2006;Martiny et al, 2006;Thompson et al, 2011).…”
Section: Resultsmentioning
confidence: 59%
“…Whether this is in response to specific metabolic exchange, to changes in the oxidative levels of the cell or to general cell stress is currently unclear. Third, both Prochlorococcus strains are likely responding specifically to the presence of other cells in co-culture, through modification of the cell wall and membrane (a common occurrence in co-culture; Tai et al, 2009;Beliaev et al, 2014) and, in the case of MIT9313, increased expression of genes potentially involved in the production of or response to antimicrobial or signaling compounds (infochemicals). These include transporters and the prochlorosin and CCRG-2 gene families.…”
Section: Transcriptome Of Prochlorococcus In Co-culture D Aharonovichmentioning
confidence: 99%
“…Indeed, transcriptional analysis of a SynechococcusShewanella co-culture found that 14% of the changes in the Synechococcus transcriptome were affiliated with transport processes (Beliaev et al, 2014). Similarly, after 1 day of co-culture the relative transcript abundance of components for at two ABCtype transporters (PMN2A_1780 and PMN2A_1891) increased in Prochlorococcus, whereas another, PMN2A_1455, decreased.…”
Section: Potential For Metabolic Exchange Between Prochlorococcus Andmentioning
confidence: 99%
“…Interactions between autotrophs and heterotrophs are central to the marine food web, as heterotrophic bacteria are dependent on photosynthetically fixed organic carbon supplied by primary producers. Autotrophheterotroph interactions have been shown to impact the autotroph as well, as work in the cyanobacterium Synechococcus has shown that co-culture impacts many cellular processes including carbon metabolism and stress responses (Tai et al, 2009;Beliaev et al, 2014). Growth of Prochlorococcus-the numerically dominant phytoplankter in the world's oceans (Flombaum et al, 2013)-in culture is improved by the presence of certain heterotrophs in terms of longevity, stationary phase cell density and ability to grow from low cell density (Sher et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Beliaev et al have analyzed the photoautotroph-heterotroph interactions between a cyanobacterium and a marine facultative aerobe with transcriptome sequencing. Their results have not only provided insights into the interactions between cyanobacteria and heterotrophs but also allowed the formulation of new hypotheses on cyanobacterial-heterotrophic interactions (24). Furthermore, Men et al have characterized the interactions of a dechlorinating coculture and triculture by transcriptome and proteome analyses.…”
mentioning
confidence: 99%